Response of faba bean (Viciafaba L.) varieties to lime application in wolaita zone, Southern Ethiopia (Revista de Ciências Agroveterinárias, 2023)
Soil acidity and scarcity of faba bean varieties adapted to lower pH soils are major factors that limit faba bean production in Ethiopia. Therefore, an experiment was conducted to find the lime rate and faba bean can improve the yield of the crop. Four rates of lime (0, 2, 4, and 6 t ha–1) and five-faba bean varieties (local, Dosha, Gebelecho, Tumsa, and Bobicho) were used as treatments, which laid out as CRD with six replications. The main and interaction effects of lime rates and varieties significantly (P
Keywords: growth; phenology; root morphology; soil acidity; yield; yield components